Measuring Monetary Policy Stress for Fed District Representatives. (6th November 2015) - Bennani, Hamza
Abstract: This study provides a measure of the degree of stress that exists among Fed districts in the US. Stress in a district is defined as the difference between the desired interest rate of its representative and the actual policy rate implemented by the FOMC. I find that the degree of stress reflects the stance of the US monetary policy, a positive stress level in the 1990s (which corresponds to a policy rate higher than the desired rate of FOMC members), and a negative stress level from the 2000s (which corresponds to a policy rate lower than the desired rate of FOMC members). However, the economic and financial crisis exacerbated the degree of stress measure, suggesting an increase in monetary policy uncertainty among FOMC members from that time.